2014
DOI: 10.1093/cercor/bhu203
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Time Course of Individual Objects with MEG

Abstract: To respond appropriately to objects, we must process visual inputs rapidly and assign them meaning. This involves highly dynamic, interactive neural processes through which information accumulates and cognitive operations are resolved across multiple time scales. However, there is currently no model of object recognition which provides an integrated account of how visual and semantic information emerge over time; therefore, it remains unknown how and when semantic representations are evoked from visual inputs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
142
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(165 citation statements)
references
References 61 publications
(100 reference statements)
18
142
2
Order By: Relevance
“…It should be noted that previous studies provided some evidence for a contribution of semantic object properties to the MEG signal even at relatively early latencies (<250 ms) (Clarke et al, 2015;Coggan et al, 2016;Kaiser et al, 2016b). These studies differed from the current study in several important ways.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…It should be noted that previous studies provided some evidence for a contribution of semantic object properties to the MEG signal even at relatively early latencies (<250 ms) (Clarke et al, 2015;Coggan et al, 2016;Kaiser et al, 2016b). These studies differed from the current study in several important ways.…”
Section: Discussioncontrasting
confidence: 90%
“…Replicating previous reports, MEG sensor patterns could be used to accurately decode individual objects (Carlson et al, 2011;Carlson et al, 2013;van de Nieuwenhuijzen et al, 2013;Cichy et al, 2014;Isik et al, 2014;Clarke et al, 2015;Ritchie et al, 2015;Coggan et al, 2016;Kaiser et al, 2016a). Using representational similarity analysis, we then related MEG neural similarity to the objects' perceptual and categorical similarity.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Binder et al, 2009). Studies using EEG and MEG have identified the timing of ATL involvement within the network, revealing recurrent interactions between the left ATL, a putative integrative hub, and more posterior regions involved in perceptual processes (Clarke et al, 2011; van Ackeren MJ and Rueschemeyer SA; Clarke et al, 2014). It is also informative that stimulation of long-range fiber tracts connecting the ATL and posterior and frontal regions has been shown to disrupt semantic knowledge retrieval (Shinoura et al, 2010; Papagno et al, 2011; Von der Heide, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that visual object recognition follows an increasingly complex featural processing (Tyler et al 2004) during which conceptual knowledge evolves from a coarse-to-fine grained representation (Cichy et al 2014;Clarke et al 2011Clarke et al , 2013Clarke et al , 2014Chan et al 2011;Peelen and Caramazza 2012). This progress takes place along the hierarchical architecture of the ventral visual pathway (Liu et al 2009), which is a recurrent network that links early visual areas with lateral and medial aspects of the anterior temporal lobe (ATL), and, most rostrally, the ventral temporal pole (Kravitz et al 2013).…”
mentioning
confidence: 99%